Magnetic Field Geometry and Composition Variation in Slow Solar Winds: The Case of Sulfur - Kuroda, Natsuha (Astrophys J, 2020)
We present an examination of the first ionization potential (FIP) fractionation scenario, invoking the ponderomotive force in the chromosphere and its implications for the source(s) of slow-speed solar winds by using observations from The Advanced Composition Explorer (ACE). Following a recent conjecture that the abundance enhancements of intermediate FIP elements, S, P, and C, in slow solar winds can be explained by the release of plasma fractionated on open fields, though from regions of stronger magnetic field than usually associated with fast solar wind source regions, we identify a period in 2008 containing four solar rotation cycles that show repeated pattern of sulfur abundance enhancement corresponding to a decrease in solar wind speed. We identify the source regions of these slow winds in global magnetic field models, and find that they lie at the boundaries between a coronal hole and its adjacent active region, with origins in both closed and open initial field configurations. Based on magnetic field extrapolations, we model the fractionation and compare our results with element abundances measured by ACE to estimate the solar wind contributions from open and closed fields, and to highlight potentially useful directions for further work.